Metabolomics reveals consistency of the shoot system in Medicago truncatula by HPLC‐UV‐ESI‐MS/MS. (12th June 2015) - Fu, Fuyou; Wang, Hong Li
Summary Flavonoids not only play crucial roles in plant development and resistance, but also provide one of the major natural sources in human nutrition. To investigate the distribution of flavonoids in the shoot system of Medicago truncatula, a high‐performance liquid chromatography coupled with electrospray ionisation tandem mass spectrometer (HPLC‐ESI‐MS/MS) method was established and then applied to determine the quantitation of flavonoids in different parts of the plant. There were twenty‐two, fifteen and eleven different kinds of flavonoids identified from the flower, leaf and stem of M. truncatula, respectively. The identified constituents were either aglycone or glycosides of the typical flavonoid backbones, such as myricetin, quercetin, luteolin, kaempferol, tricin, apigenin and laricitrin. It was found that the shoot system of M. truncatula can be differentiated by flavonoids in terms of structures and contents. Our results provide instruction to utilise the shoot system of legume crops as fodder and herb medicine in the future.